A (in)visibilização das mulheres no Curso Filosofia – licenciatura da Universidade Federal de Santa Maria/RS - Seiffert, Thays de Lima (2024)
This dissertation was developed in the Master's Degree in Education, linked to the Graduate Program in Education at the Federal University of Santa Maria (UFSM/RS), in Research Line 2: Public Educational Policies, Educational Practices and their Interfaces. The study addresses gender issues in the teaching of philosophy, with a focus on the Philosophy Degree Course at UFSM, from 1970 to 2020. The main objective was to investigate how the (in)visibility of women in this course occurred and still occurs. This is qualitative research, based on the analysis of institutional documents and semi-structured interviews. The documents analyzed over the 60 years of the course's existence include data on entrants, graduates and the Pedagogical Course Projects (PPC). The semi-structured interviews were conducted with five women - four former students and one still a student. To analyze the data, we used the Textual Discourse Analysis (TDA) method proposed by Roque Moraes and Maria do Carmo Galiazzi (2011). The theoretical framework of the research is composed of philosophers who approach gender, philosophy teaching and teacher training, including Joan Scott (1995), Judith Butler (2022), Juliana Aggio (2017), Megue Magalhães de Andrade (2017), Maria Luisa Ribeiro Ferreira (Org, 2010), Sandra Regina Goularte Almeida (2002), Graziela Rinaldi da Rosa (2012), Susana de Castro (2014), bell hooks (2018), Angela Davis (1981), among others. From the research data and the theoretical framework, it was possible to understand how this reflects on the history of philosophy, as well as how it was built on the basis of systematic exclusions, especially with regard to the presence of women in philosophical thought. The absence of female philosophers in curricula and the difficulty of academic recognition for women working in the field show how the philosophical tradition has consolidated a predominantly male narrative. This erasure not only shapes the perception of who can and cannot philosophize, but also restricts the possibilities for questioning and broadening the philosophical field.